(untitled) (Development Service Industry Management, 2024)
The article discusses the evolution of the concept of economic security of an enterprise, which has undergone five main stages of development—from the initial to the modern, where ensuring economic security has become a comprehensive and multifunctional process. The main threats, risks, and key events that influenced the formation of the concept of economic security are explored, including globalization, technological changes, economic crises, and modern challenges such as the COVID-19 pandemic and military conflicts. The approaches to defining economic security proposed by various authors are analyzed, and the main focuses are identified: financial stability, harmonization of interests with the external environment, protection of resources, and the ability to adapt to changes. The article emphasizes that economic security is a complex characteristic of the financial and economic state of an enterprise, which ensures stability and protection from internal and external threats. Special attention is paid to the principles of managing economic security, among which are: comprehensiveness, systemic approach, preventiveness, adaptability, economic feasibility, continuity, and personal responsibility. In conclusion, measures are proposed for improving the management of economic security in enterprises, taking into account modern trends and challenges.